Factors influencing clinical reasoning competence in nursing students - Kim, Jinju; Kang, Gyun-Young (Edelweiss Applied Science and Technology, 2024)
This study is a descriptive survey research aimed at identifying the factors influencing clinical reasoning competence among nursing students. The participants were 553 third-year students from nursing programs at three universities located in the K region of South Korea. The collected data were analyzed using the SPSS 23.0 program, employing Pearson’s correlation coefficient and multiple regression analysis. According to the research results, the factors affecting the participants’ clinical reasoning competence were found to be communication skills (β = 0.23, p = 0.000), problem-solving processes (β = 0.50, p = 0.000), and self-efficacy (β = 0.10, p = 0.008). Therefore, it is necessary to assess the effectiveness of various educational programs and teaching methods for improving clinical reasoning competence. The study suggests developing and researching programs focused on enhancing communication skills, self-efficacy, and problem-solving processes to improve clinical reasoning competence among nursing students.